The Spices, Western Imperialism, and The Changes of Maritime Power in The Indonesian Archipelago - Sulistiyono, Singgih Tri; Amaruli, Rabith Jihan (Journal of Maritime Studies and National Integration, 2024)
This article discusses the spices, western imperialism, and the changes of maritime power in the Indonesian archipelago. Through reading historical literature, this article finds that spices from the Indonesian archipelago entered the global market along with the development of sea trade routes between India and China in the early century AD. However, spices are commodities that have been traded long before AD. People in ancient cultural centres such as Egypt, India, Greece and Rome used spices for various purposes, including cooking spices, preserving mummies, health and to overcome disease outbreaks. Apart from India, in 16th and 17th, the archipelago is one of the important spice producing regions in the world, which was driven by the maritime power of the archipelago at that time. As an important and expensive commodity, spices have become legendary items that encourage various parties to master them, including Europeans. In the Western world, spices are seen as a trading commodity because of their expensiveness, rarity and efficacy. Economic, cultural and political dynamics in Europe have encouraged ocean exploration to gain direct access to spice producers in the Eastern world, including the archipelago. This also resulted in the birth of Western imperialism and colonialism in Asia, especially the archipelago. In the 18th century, Western domination changed the map of maritime powers in the archipelago, marked by the significantly declining role of indigenous maritime powers.